Kebijakan Negara Terhadap Agama Lokal â€œTowani Tolotangâ€ di Kabupaten Sidrap, Sulawesi Selatan - HASSE, HASSE (Jurnal Studi Pemerintahan, 2010)
This research aims to find out which political position after a limitation of the Towani Tolotang aboutreligion in Indonesia. This research is based on research on Tolotang in religion Towani in SidenrengRappang Region. Tolotang is a local religious Towani which still survive in the midst of numerousattempts genocide against them. This effort is carried out not only from groups or circles but allsofrom the presence of religion-the religion of non-official, but also occur from the regulation of Staterecognisedreligions. Although Towani Tolotang which is constantly experiencing growth in quantity,but remains under the threat that must be faced. Thus, the existence of the Towani Tolotang neverescapes the various forms of discrimination. Discrimination experienced by Towani Tolotang camefrom two directions. The first of them and denouncing society second is discrimination presented byformat by the Government through a wide variety of regulations that limit the movement of theTowani Tolotang in developing his teachings.